Synthesis of 1, 3-dioleoyl-2-arachidonoylglycerol-rich structured lipids by lipase-catalyzed acidolysis of microbial oil from Mortierella alpina. (November 2017) - Abed, Sherif M.; Zou, Xiaoqiang; Ali, Abdelmoneim H.; Jin, Qingzhe; Wang, Xingguo
Graphical abstract: Highlights: 1, 3-Dioleoyl-2-arachidonoylglycerol-rich SLs were successfully produced. UFAs content at sn -1, 3 positions of SLs increased from 60.63 to 84.00%. ARA content at the sn -2 position in SLs accounted for 49.71%. OA content at sn -1, 3 positions of SLs increased from 2.35 to 47.05%. Such SLs enriched with UFAs have potential applications in the infant formula industry. Abstract: Microbial oils (MOs) have gained widespread attention due to their functional lipids and health promoting properties. In this study, 1, 3-dioleoyl-2-arachidonoylglycerol-rich structured lipids (SLs) were produced from MO and oleic acid (OA) via solvent-free acidolysis catalyzed by Lipozyme RM IM. Under the optimal conditions, the content of unsaturated fatty acids (UFAs) increased from 60.63 to 84.00%, while the saturated fatty acids (SFAs) content decreased from 39.37 to 16.00% at sn -1, 3 positions in SLs. Compared with MO, arachidonic acid (ARA) content at the sn -2 position of SLs accounted for 49.71%, whereas OA was predominantly located at sn -1, 3 positions (47.05%). Meanwhile, the most abundant triacylglycerol (TAG) species in SLs were (18:1-20:4-18:1), (20:4-20:4-18:1), (18:1-18:2-18:1), (18:1-18:2-18:0) and (24:0-20:4-18:1) with a relative content of 18.79%, 11.94%, 6.07%, 5.75% and 4.84%, respectively. Such novel SLs with improved functional properties enriched with UFAs are highly desirable and have the potential to be used in infant formula.